Theoretical and Experimental Study on the Ultrasonic Defrosting Technology of a Quick-freezing Cooling Fan - Zuo Jiandong; Tao Tangfei; Jing Jiliang; Liu Xiaojiang; Xu Guanghua; Yang Yifan (Zhileng xuebao)
The values of excitation shear stress for frosting cream from ultrasonic high-frequency vibration were calculated using the finite element software COMSOL, and compared with the maximum adhesion stress obtained theoretically to demonstrate the feasibility of ultrasonic high-frequency vibration defrosting technology. Meanwhile, the defrosting effects of three kinds of the vibration structure, i.e., monoblock type, T-shaped and L-shaped, of a quick-freezing cooling fan were experimentally compared and analyzed under the conditions that cold storage temperature was 20 ℃, humidity was 95%, the ultrasonic frequency was 38.76 kHz, and the loading mechanism was vibrating 10 s for every 50 s. The results show that the ultrasonic has a significant inhibitory effect on the frost on the fin surface under the working condition of high humidity and low temperature, so that the quick-freezing cooling fan can operate for a long time continuously and its efficiency is significantly improved. In addition, the vibration with the structure of the monoblock type has better defrosting effect than that with T- and L-shaped.